2022
DOI: 10.29309/tpmj/2022.29.05.6543
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic correlation of portal vein diameter with gender in population of Lahore.

Abstract: Objective: To determine the reference values of normal portal vein diameter in correlation to gender in population of Lahore. Study Design: Cross Sectional study. Setting: Ultrasound Lab University of Lahore and Gondal Complex Lahore. Period: 5th October 2020 to 13th April 2021. Material & Methods: Sample size of my study were 164 males and 143 females. Simple random sampling was conducted. Healthy Individual with normal body mass index, both (male and female) individuals in fasting state and age between (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This study revealed a strong, statistically significant correlation between BMI and the PV diameter ( P = .022; Table 5), which is consistent with the findings of the studies by Chand and Jaradi 10 and Luntsi et al, 12 which revealed a positive correlation between BMI and the PV diameter. 1 Aqeel et al 11 concluded that BMI is statistically correlated with the PV diameter in female participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study revealed a strong, statistically significant correlation between BMI and the PV diameter ( P = .022; Table 5), which is consistent with the findings of the studies by Chand and Jaradi 10 and Luntsi et al, 12 which revealed a positive correlation between BMI and the PV diameter. 1 Aqeel et al 11 concluded that BMI is statistically correlated with the PV diameter in female participants.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in contrast with those of the studies by Akanni et al, 2 Geleto et al, 4 and Rapaccini et al, 15 which showed a statistically significant association between sex and the PV diameter. Aqeel et al 11 proposed that the association was only present between female sex and PV diameter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower plasma concentrations generally lead to a lower signalto-noise ratio. The smaller vessel size in women 24 and the higher needle/vein size ratio may also contribute to a higher risk of extravasation in women. Furthermore, the lower blood volume in women 25 will likely increase plasma contrast agent levels.…”
Section: Distributionmentioning
confidence: 99%